2016
DOI: 10.3233/aac-160008
|View full text |Cite
|
Sign up to set email alerts
|

Firewall configuration: An application of multiagent metalevel argumentation

Abstract: Abstract. Firewalls are an important tool in the assurance of network security. Packet filtering firewalls are configured by providing a set of rules that identify how to handle individual data packets that arrive at the firewall. In large firewall configurations, conflicts may arise between these rules. Argumentation provides a way of handling conflicts such that their origin is illuminated, and hence can help a system administrator understand the effects of a given configuration. To show how argumentation mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…It was shown that this was possible and that the performance of Gorgias was comparable, on specialized tasks, to state of the art approaches dedicated to network configuration management [53]. In another work [1], following a similar approach of formulating firewalls through argumentation, the authors provided a framework where explanations of the behaviour of the firewalls can be documented and exploited by the administrators and users of the network. Recently, Gorgias was used to study another problem in the area of cyber security, namely that of trying to understand cyber attacks on the Internet and attribute to them a likely source [28].…”
Section: Real-life Applications Of Gorgiasmentioning
confidence: 99%
See 4 more Smart Citations
“…It was shown that this was possible and that the performance of Gorgias was comparable, on specialized tasks, to state of the art approaches dedicated to network configuration management [53]. In another work [1], following a similar approach of formulating firewalls through argumentation, the authors provided a framework where explanations of the behaviour of the firewalls can be documented and exploited by the administrators and users of the network. Recently, Gorgias was used to study another problem in the area of cyber security, namely that of trying to understand cyber attacks on the Internet and attribute to them a likely source [28].…”
Section: Real-life Applications Of Gorgiasmentioning
confidence: 99%
“…S 1 1,3 is refined with x 6 that narrows down the selected options to O 1 and O 6 (row 2). S 1 1,2,8 is refined with x 9 that narrows down the selected options to O 2 (row 6). Moreover, the table shows the case of a combined scenario where the conditions of both of the basic scenarios hold at the same time.…”
Section: High-level Development Of Gorgias Applicationsmentioning
confidence: 99%
See 3 more Smart Citations